The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.2190/k8q8-5549-0y4k-ugg0
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Aging: A Comparative Analysis of Young Adults from the United States and Germany

Abstract: Social and cultural attitudes toward aging provide a framework for assessing one's own aging experiences as well as one's attitudes toward older men and women. Ageism, or prejudicial attitudes and discriminatory practices toward older adults (Butler, 1980), has been found to be widespread around the world. This study focuses on a comparative analysis of the attitudes of young adults from Germany and the United States. Specifically, the purpose of this study was to evaluate similarities and differences in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 22 publications
9
75
1
2
Order By: Relevance
“…The individualistic culture (e.g., American culture) due to the endorsement of self-centered satisfaction and interest, as well as freedom and individuality (Wang & Mallinckrodt, 2006), the individualistic culture (e.g., American culture) is increasingly youth-oriented with a negative bias toward older individuals (Barak, Mathur, Lee, & Zhang, 2001;McConatha, Schnell, Volkwein, Riley, & Leach, 2003;Nisbett, 2003). In contrast, Eastern collectivistic cultures (e.g., Chinese culture) are significantly more older-oriented, such that they place a stronger emphasis on honoring and supporting older people, committing oneself to family obligations, social interdependence, and self-sacrifice (Cuddy, Norton, & Fiske, 2005;Markus & Kitayama, 1991;Nisbett, 2003).…”
Section: The Current Inconsistencymentioning
confidence: 99%
“…The individualistic culture (e.g., American culture) due to the endorsement of self-centered satisfaction and interest, as well as freedom and individuality (Wang & Mallinckrodt, 2006), the individualistic culture (e.g., American culture) is increasingly youth-oriented with a negative bias toward older individuals (Barak, Mathur, Lee, & Zhang, 2001;McConatha, Schnell, Volkwein, Riley, & Leach, 2003;Nisbett, 2003). In contrast, Eastern collectivistic cultures (e.g., Chinese culture) are significantly more older-oriented, such that they place a stronger emphasis on honoring and supporting older people, committing oneself to family obligations, social interdependence, and self-sacrifice (Cuddy, Norton, & Fiske, 2005;Markus & Kitayama, 1991;Nisbett, 2003).…”
Section: The Current Inconsistencymentioning
confidence: 99%
“…Literature review demonstrated that various studies stressed that the attitudes of female students towards ageism were more positive than the attitudes of male students (McConatha and Huba, 1999: 166;McConatha, Schnell, Volkwein, Riley and Leach, 2003;Fitzgerald, Wray, Halter, Williams and Supiano, 2003: 850). Furthermore, a study by Güven, Ucakan Muz and Efe Ertürk (2012: 102) determined that female students had a positive attitude towards the elderly and that there was a statistically significant difference between the groups and the restricting life of the elderly sub-dimension (p<0.05).…”
Section: Attitudes Of Social Work Students Towards Ageismmentioning
confidence: 99%
“…Ageism is a product of society (Angus & Reeve, 2006;Mautner, 2007; McConatha, Hayta, Rieser-Danner, McConatha, & Polat, 2004;McConatha, Schnell, Volkwein, Riley, & Leach, 2003;Nelson, 2002;Palmore, 1990;Stone, 2003;Thomas & Shute, 2006;Yang, Kleinman, Link, Phelan, Lee, & Good, 2007). Accumulated views stem from deep-rooted beliefs, influenced by social, political, and economic factors (Angus & Reeve, 2006;Thomas & Shute, 2006).…”
Section: Ageism As a Consequence Of Society And Culturementioning
confidence: 99%
“…Saucier (2004) stated that "youth is worshipped" (p. 420) in this society, and its prevalence is associated with power and acceptance. The media, magazines, and advertisements are partially responsible for this obsession (Nelson, 2002;McConatha et al, 2004;McConatha et al, 2003;Robinson, Gustafson, & Popovich, 2008;Saucier, 2004). These sources of information unconsciously feed on youthfullooking skin, healthy hair, and muscular or toned physiques.…”
Section: Ageism As a Consequence Of Society And Culturementioning
confidence: 99%